Learn AppleScript: The Comprehensive Guide to Scripting and Automation on Mac OS X, Third Edition - Sanderson, Hamish (Apress, 2012)
Welcome to the third edition of Learn AppleScript: The Comprehensive Guide to Scripting and Automation on Mac OS X. This book will teach you the principles and practices of controlling the many “AppleScriptable” Mac OS X applications using the AppleScript scripting language included in Mac OS X. The title of this book represents a challenge: just how do you create a comprehensive guide to a subject as broad and deep as automating your Mac with AppleScript? While we do cover every aspect of the AppleScript language in extensive detail, obviously we cannot hope to cover every last scriptable application on the market today. Instead, we will explain the core principles by which all scriptable applications operate, before exposing you to a broad range of very different applications—from simple and familiar tools such as TextEdit and Finder, through popular lifestyle applications such as Mail and iTunes, and on to professional productivity programs such as Microsoft Office and Adobe InDesign. Although you may not use all of these applications in your daily routine, we hope that you will take the time to explore them here. Exploring the wide range of applications covered here will help to familiarize you with the many similarities (and differences) found among scriptable applications today—knowledge that will provide essential guidance and inspiration as you go on to learn and use other scriptable applications for yourself. While this book is designed for Mac users who have never scripted before, we have ensured that there is plenty of material here to engage more experienced AppleScripters, as well as professional programmers coming to AppleScript from other languages. So without further ado, let’s look at how you can get the most out of this book whatever your background is.